Expression of Survivin in Patients With Refractory Rheumatoid Arthritis in a Chinese Population - Xian Ming LONG; Jin Wei CHEN; Wen Jing WANG; Jia WANG (Archives of Rheumatology, 2014)
Objectives: This study aims to investigate whether the expression of survivin is associated with refractory rheumatoid arthritis (RA) among Chinese patients. Patients and methods: We evaluated the expression of survivin in serum and synovial tissues in 60 patients of RA and 20 healthy controls. Rheumatoid arthritis patients were divided into three groups: 20 patients in the untreated group, 20 patients in the treatment-responsive group and 20 patients in the treatment refractory group. Serum concentrations of survivin in four groups were measured by enzyme-linked immunosorbent assay. Clinical features and laboratory test results including disease duration, complete blood count, erythrocyte sedimentation rate, C-reactive protein, rheumatoid factor and anti-cyclic citrullinated peptide antibody were recorded. Expression levels of survivin in synovial tissue of all 51 samples were tested by immunohistochemical technique. Results: The survivin level was significantly higher in the refractory group than healthy controls (270.04±23.03 pg/ml vs. 116.68±19.07 pg/ml, p<0.05) and treatment-responsive group (270.04±23.03 pg/ml vs. 127.37±11.42 pg/ml, p<0.05). The survivin level in refractory RA patients was positively correlated with the Disease Activity Score 28. Immunohistochemical analysis revealed that survivin expression was significantly higher in the synovial tissues of refractory RA patients compared to treatment-responsive patients and healthy controls. Conclusion: The results of this study showed that survivin is overexpressed in refractory RA patients and the serum survivin level is correlated with disease activity.